Peningkatan Kapasitas Evaluasi Rencana Pembangunan Jangka Menengah (RPJM) Kabupaten Nagan Raya Tahun 2017-2022 - Cut Asmaul Husna; Asmaul Husna; Yuhdi Fahrimal; Reni Juliani; Fadhil Ilhamsyah (Universitas Teuku Umar, 2022)
Evaluation of the Medium Term Development Plan (RPJM) of Nagan Raya Regency for 2017-2022 is information that generally describes the general description of the results of the assessment of the RPJM regarding the achievement of Financial Performance and Analysis of Achievement Indicators of vision and mission, substance in accordance with targets and performance indicators as well as RPJM Systematics as materials to support development planning in Nagan Raya Regency in the future. This paper aims to see the results of the Nagan Raya Regency RPJM Evaluation which objectively provides an assessment with the data presented sourced from the Nagan Raya Regency RPJM documents for 2017-2022 and other planning documents for accountable comparisons for improving the quality of development planning in the future. come.